2017
DOI: 10.1158/1055-9965.epi-17-0358
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pulmonary Toxicity of Electronic Cigarettes in the Context of Smoking: A Focus on Inflammation

Abstract: The use of electronic cigarettes (e-cigs) is increasing rapidly, but their effects on lung toxicity are largely unknown. Smoking is a well-established cause of lung cancer and respiratory disease, in part through inflammation. It is plausible that e-cig use might affect similar inflammatory pathways. E-cigs are used by some smokers as an aid for quitting or smoking reduction, and by never smokers (e.g., adolescents and young adults). The relative effects for impacting disease risk may differ for these groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 257 publications
(241 reference statements)
5
76
0
3
Order By: Relevance
“…5,6 Another study found increase in inflammatory signalling molecules upon inhalation, in resemblance to what is seen in tobacco smoking. 9 Clinical studies evaluating the safety and risk profile of e cigarette use in humans are limited and most the current data is obtained from in vitro studies on cultured cells and in vivo experiments in animal models. The short-term in-vitro studies using cultured cells have shown that exposure to e liquid or aerosols reduces cell viability, induces cytokine production and causes oxidative stress.…”
Section: Cas E R Ep Ortmentioning
confidence: 99%
“…5,6 Another study found increase in inflammatory signalling molecules upon inhalation, in resemblance to what is seen in tobacco smoking. 9 Clinical studies evaluating the safety and risk profile of e cigarette use in humans are limited and most the current data is obtained from in vitro studies on cultured cells and in vivo experiments in animal models. The short-term in-vitro studies using cultured cells have shown that exposure to e liquid or aerosols reduces cell viability, induces cytokine production and causes oxidative stress.…”
Section: Cas E R Ep Ortmentioning
confidence: 99%
“…In addition, it has been established that EL contains carcinogenic metals such as cadmium, chromium, nickel, lead, and manganese [15]. Flavorings in the EL, intended to appeal to consumers, also contain lung toxins like diacetyl and diketones [16]; the former of which is associated with bronchiolitis obliterans, commonly known as popcorn lung disease [17]. Toxicity is marked in all flavorings.…”
Section: Introductionmentioning
confidence: 99%
“…ECs are not entirely free of these compounds and may also contain propylene glycol, glycerol, liquid flavors, heavy metals, nicotine, and volatile organic compounds (VOCs). 6,7 Formaldehyde, a product of propylene glycol and glycerol vapor degradation, is a cancer-causing substance that may form if the EC liquid overheats or not enough liquid reaches the heating element (known as a dry puff). Formaldehyde can cause an increase in airway inflammatory markers up to 10 times more than traditional cigarettes.…”
Section: Intentional Chemical Additives and Unintentional Byproductsmentioning
confidence: 99%
“…Formaldehyde can cause an increase in airway inflammatory markers up to 10 times more than traditional cigarettes. 6 ECs aerosolize nicotine, and concentrations are typically between 6 to 24 mg/mL but can be as high as 100 mg/mL. 8 Online vaping and EC stores sell a variety of EC liquids, nicotine salts, and vaping liquids containing cannabidiol (CBD) and tetrahydrocannabinol (THC).…”
Section: Intentional Chemical Additives and Unintentional Byproductsmentioning
confidence: 99%